2015
DOI: 10.18632/oncotarget.4226
|View full text |Cite
|
Sign up to set email alerts
|

The indirect NMDAR inhibitor flupirtine induces sustained post-ischemic recovery, neuroprotection and angioneurogenesis

Abstract: N-methyl-D-aspartate receptor (NMDAR) activation induces excitotoxicity, contributing to post-stroke brain injury. Hitherto, NMDAR deactivation failed in clinical trials due to insufficient pre-clinical study designs and drug toxicity. Flupirtine is an indirect NMDAR antagonist being used as analgesic in patients. Taking into account its tolerability profile, we evaluated effects of flupirtine on post-stroke tissue survival, neurological recovery and brain remodeling. Mice were exposed to stroke and intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The intrinsic capacity of brain repair can be efficiently stimulated by exogenous therapeutic interventions, e.g., by physical exercise, delivery of growth factors, cell-based biologicals or pharmacological compounds, which in rodent and primate models of stroke were shown to enhance neurological recovery (Bacigaluppi et al, 2009 ; Reitmeir et al, 2011 , 2012 ; Jaeger et al, 2015 ; Wang et al, 2016 ). Neurological recovery in the experimental setting can be defined as regain of lost function of the paretic limb as compared to a baseline defined previous to the stroke, which should not be confused with neurological compensation (Murphy and Corbett, 2009 ), in which other parts of the limbs (e.g., shoulder or the non-paretic limb) are recruited to complete a task.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic capacity of brain repair can be efficiently stimulated by exogenous therapeutic interventions, e.g., by physical exercise, delivery of growth factors, cell-based biologicals or pharmacological compounds, which in rodent and primate models of stroke were shown to enhance neurological recovery (Bacigaluppi et al, 2009 ; Reitmeir et al, 2011 , 2012 ; Jaeger et al, 2015 ; Wang et al, 2016 ). Neurological recovery in the experimental setting can be defined as regain of lost function of the paretic limb as compared to a baseline defined previous to the stroke, which should not be confused with neurological compensation (Murphy and Corbett, 2009 ), in which other parts of the limbs (e.g., shoulder or the non-paretic limb) are recruited to complete a task.…”
Section: Introductionmentioning
confidence: 99%
“…Flupirtine is well known for its significant powerful anti-oxidative, anti-apoptotic, and neuroprotective effects in vitro and in vivo. The effectiveness of the chosen daily dose of flupirtine (30 mg/kg per os) has been demonstrated in testing for anti-nociceptive, anticonvulsant, and anti-apoptotic activity in rodents [ 23 , 24 , 25 , 26 , 27 ]. This study is the first to evaluate the use of flupirtine as potential treatment for CLN3 disease in an animal model, i.e., in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Retigabine inhibits SD in mild, but not severe oxygen-glucose deprivation (OGD) model. Kv7 activators have been shown to reduce neuronal damage following experimental ischemia, where SD could potentially contribute to progression of the lesion 46,47 . We examined whether the Kv7 activator retigabine can also inhibit SD generated during the experimental in vitro ischemia model of oxygen- Figure 7.…”
Section: Effect Of Pharmacological Inhibition and Activation Of Kv7 Cmentioning
confidence: 99%
“…We showed that retigabine could delay SD onset following submaximal OGD stimulation. Interestingly, Kv7.2 activators are neuroprotective in experimental ischemia and brain trauma studies 46,47,51,59,60 , and the anti-SD properties of the activator may contribute to these neuroprotective effects. It should be noted that only a relatively high, sedating, drug concentration effectively inhibited SD, and the drug may therefore be of limited prophylactic utility.…”
Section: Sd Modulation By Kv72 Activitymentioning
confidence: 99%